Las Fábulas en la Práctica de Valores morales en las niñas de segundo grado de Educación Primaria, Institución Educativa N° 81007 “Modelo” - Trujillo, 2016 - Lezama Villavicencio, Johana Jamali (2017)
The main objective of this research is to demonstrate that the fables in the practice of moral values have improved the behavior in the students of the second degree of IE "Maria Model Virtue" of Trujillo - 2016. The research is of quasi experimental design with Group Control and experimental group. This study had as sample of study 28 students in the group in the experimental group and 25 students in the control group, whose ages vary between 7 and 8 years of age, being the experimental group to whom the research project was applied based on Fables in the practice of moral values; Using as an application scenario the facilities of the Educational Institution. The results obtained after having applied the pretest, reveal that the control group presents almost the same level of behavior in the practice of moral values as the experimental group; Finally with the application of the postest, the students of the experimental group managed to obtain a significant improvement in the behavior of the moral values practice of the students of the second grade of primary education as opposed to the control group.